An empirical study of Women Entrepreneurship motivational factors in Botswana - Sibanda, Khulekani (International Journal of Business, Management and Economics, 2020)
Women entrepreneurship plays a significant role in the economic development of a nation’s economy; thus, this study was set up to study the main motivations of women entrepreneurs in Botswana. The findings revealed that the women entrepreneurs in Botswana are motivated by a range of issues to start business both the pull and push factors. It was thus recommended that the government should provide sufficient infrastructural facilities along with the routine concessions and incentives to women entrepreneurs in the region. For better results, there should be co-ordination among the various agencies involved, without any overlapping of the functions. Flexibility and timely assistance by the financial institutions would help the women entrepreneurs to survive profitably, despite the entry of multinationals into the country and region. The officials of both the government and the banks should take initiative in the matter of financial and promotional assistance to the new and prospective women entrepreneurs.